2019
DOI: 10.1785/0120180322
|View full text |Cite
|
Sign up to set email alerts
|

Joint Body‐ and Surface‐Wave Tomography of Yucca Flat, Nevada, Using a Novel Seismic Source

Abstract: In preparation for the next phase of the Source Physics Experiments, we acquired an active‐source seismic dataset along two transects totaling more than 30 km in length at Yucca Flat, Nevada, on the Nevada National Security Site. Yucca Flat is a sedimentary basin which has hosted more than 650 underground nuclear tests (UGTs). The survey source was a novel 13,000 kg modified industrial pile driver. This weight drop source proved to be broadband and repeatable, richer in low frequencies (1–3 Hz) than traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…(Bottom left) Theoretical velocities (gray) compared with P well log (blue) and S estimate from Toney et al. (2019) (green). (bottom right).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Bottom left) Theoretical velocities (gray) compared with P well log (blue) and S estimate from Toney et al. (2019) (green). (bottom right).…”
Section: Discussionmentioning
confidence: 99%
“…A WKBJ algorithm used to calculate travel times from the source to the fiber channel locations (Stockwell, 2008). The parametrization assumes that the velocity increases with depth, which is reasonable given the Yucca Flat velocity structure (Toney et al., 2019; Wagoner & Prothro, 2020). The advantage of a grid search is that it provides a robust indication of the error.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Borehole data and gravity studies have revealed much about the geologic structure such as its depth, which at its deepest point in the southern part of the basin is over 2 km, and shape, with the long axis of the basin being oriented north-south. The basin fill is composed of Quaternary alluvium overlying Tertiary-aged tuffs that sit above Paleozoic basement, mostly comprised of sedimentary units [2], [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…Other gravity data interpretation approaches to modelling the basement morphology use the Tikhonov regularized inversion method (Tikhonov and Arsenin 1977) to obtain the basement geometry, assuming a density contrast. With these approaches, the subsurface is generally discretized into a grid of columnar prisms of known horizontal dimensions and known density, and the parameters to be estimated in the inversion model consist of the thicknesses of the columns.…”
Section: Introductionmentioning
confidence: 99%